Factorization of Boundary Value Problems Using the Invariant Embedding Method - Henry, Jacques; Henry, Jacques; Ramos, A. M. (Elsevier Science, 2016)
Factorization Method for Boundary Value Problems by Invariant Embedding presents a new theory for linear elliptic boundary value problems. The authors provide a transformation of the problem in two initial value problems that are uncoupled, enabling you to solve these successively. This method appears similar to the Gauss block factorization of the matrix, obtained in finite dimension after discretization of the problem. This proposed method is comparable to the computation of optimal feedbacks for linear quadratic control problems.Develops the invariant embedding technique for boundary value problemsMakes a link between control theory, boundary value problems and the Gauss factorizationPresents a new theory for successively solving linear elliptic boundary value problemsIncludes a transformation in two initial value problems that are uncoupled